Structure–function analysis of the plasma membrane- localized Arabidopsis defense component ACD6 - Lu, Hua; Liu, Yang; Greenberg, Jean T. (Wiley, 2005)
The ACCELERATED CELL DEATH 6 (ACD6) protein, composed of an ankyrin-repeat domain and a predicted transmembrane region, is a necessary positive regulator of Arabidopsis defenses. ACD6 overexpression confers enhanced disease resistance by priming stronger and quicker defense responses during pathogen infection, plant development or treatment with an agonist of the key defense regulator salicylic acid (SA). Modulation of ACD6 affects both SA-dependent and SA-independent defenses. ACD6 localizes to the plasma membrane and is an integral membrane protein with a cytoplasmic ankyrin domain. An activated version of ACD6 with a predicted transmembrane helix mutation called ACD6-1 has the same localization and overall topology as the wild-type protein. A genetic screen for mutants that suppress acd6-1-conferred phenotypes identified 17 intragenic mutations of ACD6. The majority of these mutations reside in the ankyrin domain and in predicted transmembrane helices, suggesting that both ankyrin and transmembrane domains are important for ACD6 function. One mutation (S638F) also identified a key residue in a putative loop between two transmembrane helices. This mutation did not alter the stability or localization of ACD6, suggesting that S635 is a critical residue for ACD6 function. Based on structural modeling, two ankyrin domain mutations are predicted to be in surface-accessible residues. As ankyrin repeats are protein interaction modules, these mutations may disrupt protein–protein interactions. A plausible scenario is that information exchange between the ankyrin and transmembrane domains is involved in activating defense signaling.
Keywords: ankyrin repeats; camalexin; disease resistance; Pseudomonas syringae; salicylic acid; Arabidopsis